Relationship between smartphone addiction and loneliness among adolescents - Dikeç, Gül; Yalnız, Tuğçe; Bektaş, Berna; Turhan, Atakan; Çevik, Sümeyye (Journal of Dependence, 2017)
Objective: The aim of this study was to examine the relationship between smartphone addiction and loneliness in a group of high school students in İzmir.Method: The data were collected from 465 students using a Personal Information Form, the Smartphone Addiction Scale-Short Form (SAS-SF) and the UCLA Loneliness Scale.Results: The average age of the participant students was 16.15 ± 1.04, with males constituting 42.8% and females constituting 57.2% of the study sample. The students’ average scores on the SAS-SF and UCLA were 28.14 ± 11.54 and 53.72 ± 5.42, respectively. A significant positive relation was found between SAS-SF and UCLA (r: .202, p: 0.00), and while no significant correlation was observed between SAS-SF, age, and GPA (p > 0.05). A positive moderate correlation was found in terms of the daily duration of smartphone usage (r: .409, p: 0.00).Conclusion: The study found that students who feel a sense of loneliness tend to use smartphones a lot and are at risk of smartphone addiction. It is recommended that addiction community mental health nurses take preventive measures against smartphone addiction to protect and improve the mental health of the students.
Keywords: community mental health nurse; high school students; loneliness; smartphone addiction